The prevalence of neck pain, back pain and low back pain among third-year medical students at universities in the metropolitan region of Porto Alegre in times of Covid-19 (International Seven Journal of Health Research, 2024)
Objective: To determine the prevalence of cervical, dorsal and lumbar pain caused by switching to remote classes during the Covid-19 pandemic. Methods: This is an original article based on a cross-sectional study among men and women over the age of 18 who are third-year medical students to assess the incidence of neck pain, back pain and low back pain, using online forms with questions about physical and mental health. Results: Around 60% of the participants said they had adapted their study environment because of the remote classes, with a further 70% saying they were attending classes in the office, with their backs poorly supported. In addition, there was a low number of overweight students who performed daily stretching. Conclusion: The data was analyzed using tables, descriptive statistics and the statistical test: Mann-Whitney Non-parametric Test and Krsukal-Wallis Non-parametric Test and the importance of further research was highlighted, given that this research topic is essential for the prevention of possible comorbidities.